Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis dan Aktivitas Siswa Melalui Pembelajaran Kooperatif Learning Tipe Jigsaw di Kelas II Sekolah Dasar - Hani Handayani (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2017)
Abstract The problems in this research are the low learning activity experienced by the students and the students’ problem solving ability of mathematics. The purpose of this research is to improve the students’ ability in solving mathematical problems and the students’ learning activities through Jigsaw cooperative learning, particularly on the multiplication materials in second grade class of SDN Tangsungsari I, Kabupaten Sumedang. This research is a classroom action research conducted in two cycles. The subjects of the study were the 33 students of 2nd grade class of SDN TanjungSari 1, Kabupaten Sumedang. The object of this research is the implementation of Jigsaw cooperative learning. The research instrument are using an essay test, which its validity and reliability has been tested, and also conducting observation on the students’ learning activity. The  results show that the average of student learning activities on the first cycle values 60. In the second cycle, the learning activitivity in the first cycle, reaching the value of 65, has been increased on the second cycle reaching the value of 80. Keywords: Learning activity, problem solving of mathematical, and cooperatife learning tipe Jigsaw.  Abstrak Permasalahan dalam penelitian ini adalah rendahnya aktivitas dan kemampuan pemecahan masalah siswa. Tujuan penelitian ini adalah untuk meningkatkan kemampuan pemecahan masalah matematika dan aktivitas siswa melaluli pembelajaran kooperatif learning tipe Jigsaw pada materi perkalian di kelas II SDN Tanjungsari 1 Kabupaten Sumedang. Metode penelitian yang digunakan adalah penelitian Tindakan Kelas dengan tindakan sebanyak sua siklus. Dalam penelitian ini instrument yang digunakan adalah tes dengan jenis soal essay yang telah diuji validasi dan reliabilitasnya dan lembar observasi untuk mengobservasi aktivitas belajar siswa. Berdasarkan hasil penelitian, diperoleh rata-rata aktivitas belajar siswa pada siklus I dengan nilai 60. Pada siklus II telah meningkat dengan nilai rata-rata 81. Demikian pula kemampuan pemecahan masalah matematika pada siklus I mendapatkan nilai 65, pada siklus kedua telah meningkat dengan nilai 80. Kata Kunci: Aktivitas belajar, kemampuan pemecahan masalah matematika siswa, dan kooperatif learning tipe Jigsaw.